How Did the Psychological Well-Being of Church of England Clergy and Laity Change From the First to the Third National COVID-19 Lockdowns? - Village, Andrew (Pastoral psychology, 2022)
The balanced affect model of psychological well-being conceptualises positive and negative affect as two separate continua and well-being as the function of these two entities. The COVID-19 pandemic lasted over two years in the United Kingdom and initially caused widespread declines in mental health and well-being. This paper tests whether such declines continued or stabilised as the pandemic lockdowns persisted. The psychological well-being of a religiously committed sample was assessed by perceived changes in affect balance (a function of negative and positive affect) using The Index of Affect Balance Change (TIBACh) from the first to the third COVID-19 lockdowns in the Church of England. The 2020 sample in the first lockdown comprised 792 stipendiary parochial clergy and 2,815 laity who were not in licensed ministry in the Church of England. A repeat survey in the third lockdown in England in 2021 collected responses from 401 equivalent clergy and 1027 equivalent laity. Both clergy and lay people showed increased proportions reporting lower positive affect and increased proportions reporting higher negative affect in the second survey, suggesting psychological well-being had continued to deteriorate as lockdowns persisted.